(3GdOdjd GdSjGMj GdEdcJQhfj dRhGQ GdeOjfI GdefhQI (B/s - (3GdTjN, fRGQ eMehO bGSes 1972- ((3LOI (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s [(3ecGf GdfTQ ZjQ eMOO(B] :s (3ecJHI QhGFY GdeedcI,s (3OGQ GdYQjT,s, 2019)
(3jYQV cJGH GdOdjd GdSjGMj GdEdcJQhfj dRhGQ GdeOjfI GdefhQI aj fbGW (B: (3YQV SjQI GdfHj Udi Gddg Ydjg hSde ef GdgLQI Edi GdhaGI, QcR Ydi LZQGajI GdSjQI GdfHhjI, Mbb eYGde GdSjQI GdfHhjI YdejG hejOGfjG, hVM GdcKjQ ef GdeYGde HGdNQGFW hGdUhQ, QHW LejY GdeYGde EdcJQhfjG HNQGFW LhLd Yf WQjb GdHGQchO, Hjf eYGde GdSjQI GdfHhjI dCcKQ ef (B200 (3ehbY(B.s
(3cTGa (B: (3UaMI (B283-289.s
(3HHdjhLQGajI (B: (3UaMI (B280-282.s
Keywords: (3GdSjQI GdfHhjI s -- (3cJH EQTGOjIs -- (3GdeOjfI GdefhQIs; (3GdeOjfI GdefhQIs -- (3cJH EQTGOjIs